2007
DOI: 10.1111/j.1939-1668.2007.tb00420.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagramming Design Research

Abstract: This paper proposes a diagramming method to help conceptualize and structure design research. In addition, it shows how the method is useful in situating the design process into larger interdisciplinary bodies of knowledge. The paper begins by defining design and research with consideration of the difference between research and fact‐finding. It then outlines common ways human beings come to know the world; these ways of knowing supply material to devise the proper research diagram for any particular topic. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Visual communication is normative to design communication practices. Many designers communicate through sketching and drawing (Ching, 2009;Lawson, 2005), and it has been suggested that visual diagramming can even be a tool leveraged in critical examination (Wang, 2007). In fact, the aforementioned CIDA Future Vision (2014) report posited that large amounts of data would provide increased opportunities for designers to "communicate complex ideas visually" (p. 6).…”
Section: Benefits Of Using Scholarly Sourcesmentioning
confidence: 99%
“…Visual communication is normative to design communication practices. Many designers communicate through sketching and drawing (Ching, 2009;Lawson, 2005), and it has been suggested that visual diagramming can even be a tool leveraged in critical examination (Wang, 2007). In fact, the aforementioned CIDA Future Vision (2014) report posited that large amounts of data would provide increased opportunities for designers to "communicate complex ideas visually" (p. 6).…”
Section: Benefits Of Using Scholarly Sourcesmentioning
confidence: 99%
“…Most scholars have defined research as the discovery of new information that expands the knowledgebase of the profession (Groat & Wang, 2002; Guerin & Dohr, 2007; Sommer & Sommer, 2002; Wang, 2007). In examining definitions of research that range from 1964 to 2007 from a variety of fields of study, including architecture, education, home economics, interior design, and psychology, terms such as “systematic,”“patient study,” and “discovery” are repeated throughout (Dickinson & Marsden, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…9. “Research … can be described as the generation of new knowledge which has application for a wide general domain…” ( Wang, 2007, p. 34 ). (Definitions cited from Informing Design, Dickinson & Marsden, 2009 ).…”
Section: Literature Reviewmentioning
confidence: 99%